Evangelization and Renewal: Embracing the Transformative Power of the Eucharist in the Modern World - Pablito A. Baybado, Sebastian Mathew Mittathanickal and (Asian Horizons, 2023)
The paper discusses the transformative theology of the Eucharist of Pope Benedict XVI in the modern world and its relevance. It emphasizes the sacrament of transformation and the purpose of the Eucharist in the transformation of individuals who partake in communion. The paper also highlights the significance of active participation in the Eucharistic sacrifice and the need for the transformative character of the Eucharist in renewing the Church and in addressing social struggles and realities. The goal is to provide principles and guidelines for incorporating the transformative character of the Eucharist in the pastoral approaches and ministries of the Church.